Submission to Science Research Council - College of Aeronautics (Cranfield) (College of Aeronautics, 1968)
Support is requested from the Science Research Council for an extension of the research facilities available for the investigation of flexural vibrations of crankshafts at the Advanced School of Automobile Engineering. Sufficient evidence exists to indicate that flexural vibrations of crankshafts are significant at certain running conditions and critical speeds of an engine. It is also possible that unaccountable failures of crankshafts in service may be explained by fatigue as a consequence of large vibrating stresses due to resonance of the bending mode. Lack of knowledge of these vibrations is such that the criteria used for the design of devices that reduce the amplitudes of vibration and noise at the critical speeds are not well founded. The results of the theoretical and experimental studies already carried out at the school are promising but they are restricted to a particular crankshaft. To fully establish the methods of analysis, to extend the analyses and to test a significant number of crankshafts of various types, it is the proposal that a Senior Research Fellow and a Research Engineer will be employed for three years. Additional test facilities and instrumentation are requested for the extension of the work in progress.